'Someday it will be the norm': physician perspectives on the utility of genome sequencing for patient care in the MedSeqProject. (January 2015) - Vassy, Jason L; Christensen, Kurt D; Slashinski, Melody J; Lautenbach, Denise M; Raghavan, Sridharan; Robinson, Jill Oliver; Blumenthal-Barby, Jennifer; Feuerman, Lindsay Zausmer; Lehmann, Lisa Soleymani; Murray, Michael F; Green, Robert C; McGuire, Amy L
Aim: To describe practicing physicians' perceived clinical utility of genome sequencing.Materials & methods: We conducted a mixed-methods analysis of data from 18 primary care physicians and cardiologists in a study of the clinical integration of whole-genome sequencing. Physicians underwent brief genomics continuing medical education before completing surveys and semi-structured interviews.Results: Physicians described sequencing as currently lacking clinical utility because of its uncertain interpretation and limited impact on clinical decision-making, but they expressed the idea that its clinical integration was inevitable. Potential clinical uses for sequencing included complementing other clinical information, risk stratification, motivating patient behavior change and pharmacogenetics.Conclusion: Physicians given genomics continuing medical education use the language of both evidence-based and personalized medicine in describing the utility of genome-wide testing in patient care.